Pin1: A New Outlook in Alzheimer's Disease - Lonati, E.; Masserini, M.; Bulbarelli, A. (Current Alzheimer Research, 2011)
Neurodegenerative diseases termed Tauopathies, including Alzheimer disease, are characterized by the presence of intraneuronal neurofibrillary tangles (NFTs), composed by hyperphosphorylated protein Tau. Peptidyl-prolyl cis/trans isomerase Pin1 plays a pivotal role in the regulation of Tau phosphorylation/dephosphorylation state. Indeed, Pin1 specifically recognizes pThr231-Pro232 motif of Tau, catalyzes its isomerisation and, in dependence of the cellular environment, promotes its dephosphorylation by PP2A phosphatase: in the dephosphorylated state Tau is able to exert its physiological activity, promoting microtubules polymerization. However, Pin1 activity in Tauopathies in which Tau is mutated can be harmful, because the isomerase can accelerate progression of the disease. Taking into account the complexity of pathways in which Pin1, under a strict regulation, exerts its biological functions, this isomerase can be consider a promising target in the improvement and design of new therapies against Tauopathies.
Keywords: Pin1 enzyme